Design and synthesis of thiahelicenes for molecular electronics - Baciu, Bianca C.; Bronk, Pawel J.; Guijarro, Albert (Frontiers in Chemistry, 2024)
The conductance of a tunneling electron through a π-conjugated molecule may be affected by the presence of different pathways in the orbital structure of the molecule, resulting in the constructive or destructive interference of the molecular wave function. This quantum interference (QI) directly translates into enhancement or suppression of conductance and offers the possibility of controlling this phenomenon through tailored synthesis. Hence, we set up synthetic methodologies to access a series of thiophene-fused helicenes with a well-defined positioning of the sulfur atoms, which control the occurrence of conducting, linearly conjugated as well as disrupted, cross-conjugated pathways. We describe these synthetic strategies and relate the expected electronic transport through our molecules to three key variables: a) the exo-/endo-topology of the S atom within the ring; b) the parity (odd/even) of the overall number of rings conforming to the helicene; and c) the size of the circuit. This series ranks from [7] to [11] fused rings, having both exo-, endo-, or mixed exo-endo-topology. Comparison of homologous dithiahelicenes with size-tunable highest occupied molecular orbital (HOMO)/lowest unoccupied molecular orbital (LUMO) energies allows us to isolate the key variable of the bond topology from other electronic properties and face the study of QI in helically conjugated molecules. Understanding and tuning the conductance in such molecular solenoids is the main purpose of this work.